Breakfast replacement with a liquid formula improves glycaemic variability in patients with type 2 diabetes: a randomised clinical trial. Issue 5 (16th January 2019) - Peng, Jiahui; Lu, Jingyi; Ma, Xiaojing; Ying, Lingwen; Lu, Wei; Zhu, Wei; Bao, Yuqian; Zhou, Jian
Abstract: There is emerging evidence that glycaemic variability (GV) plays an important role in the development of diabetic complications. The current study aimed to compare the effects of lifestyle intervention (LI) with and without partial meal replacement (MR) on GV. A total of 123 patients with newly diagnosed and untreated type 2 diabetes (T2D) were randomised to receive either LI together with breakfast replacement with a liquid formula (LI+MR) ( n 62) or LI alone ( n 61) for 4 weeks and completed the study. Each participant was instructed to have three main meals per d and underwent 72-h continuous glucose monitoring (CGM) both before and after intervention. Measures of GV assessed by CGM included the incremental AUC of postprandial blood glucose (AUCpp), standard deviation of blood glucose (SDBG), glucose CV and mean amplitude of glycaemic excursions (MAGE). After a 4-week intervention, the improvements in systolic blood pressure ( P =0·046) and time in range ( P =0·033) were more pronounced in the LI+MR group than in the LI group. Furthermore, LI+MR caused significantly greater improvements in all GV metrics including SDBG ( P =0·005), CV ( P =0·002), MAGE ( P =0·016) and AUCpp ( P <0·001) than did LI. LI+MR ( v. LI) was independently associated with improvements in GV after adjustment of covariates (all P <0·05). Our study showed that LI+MR led to significantly greater improvements in GV compared with LI, suggesting that LI+MR could be an effective treatment to alleviate glucose excursions.